Dinamika Kebijakan Internasional: Tantangan Dan Peluang Di Era Globalisasi - Annisa Ahadiani; Menur Putria Duwy; Siti Nurhayati Wergiri; Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The dynamics of international policy in the era of globalization present complex challenges and opportunities for countries throughout the world. Globalization has accelerated economic, political and cultural interconnections, but has also created dependency between countries which often triggers conflicts of interest. This article analyzes challenges, such as global competition, changing consumer tastes, and technological change, that influence international policy formulation. On the other hand, globalization also opens up opportunities for multilateral collaboration in the fields of trade, technology and handling transnational issues. Using a policy analysis approach and recent case studies, this article highlights the importance of adaptive diplomacy, strengthening global institutions, and a values-based approach in dealing with rapidly changing dynamics. The conclusion of this analysis shows that the success of international policy is highly dependent on the ability of countries to navigate global challenges with collaborative strategies that are inclusive and oriented towards long-term solution